Effects of common pharmaceutical drugs (paracetamol and acetylsalicylic acid) short term exposure on biomarkers of the mussel Mytilus spp - Piedade, Francisca (2022)
Pharmaceutical drugs in the wild may pose significant risks to non-target exposed organisms. This situation is even more troublesome for coastal marine or estuarine environments, located in the vicinity of large human conglomerates, for which the putative number of pollutants is extremely high, and the regime by which wild organisms are exposed is continuous. In addition, the number of studies addressing this issue is still scarce, despite evidences that show the potential contamination profiles and adverse biological effects in organisms from such areas. In this study, the ecotoxicity of common pharmaceutical drugs (namely paracetamol and acetylsalicylic acid) was assessed, by studying the susceptibility of the mussel species Mytilus spp to oxidative stress after being exposed for 96 h to increasing but ecologically relevant concentrations of the two mentioned pharmaceuticals (paracetamol: 0, 0.5, 5, 50, and 500 μg/L; acetylsalicylic acid: 0, 0.1, 1, 10, and 100 μg/L). The oxidative status in exposed organisms was analyzed by measuring oxidative stress biomarkers, namely catalase (CAT), glutathione-S-transferases (GSTs), and lipoperoxidation (LPO) levels, whose alteration was indicative of chemical exposure, in both digestive gland and gills of the organisms. In addition, the food uptake and the nutritional reserve status of exposed organisms were also assessed, by measuring the consumption of ingested food, and levels of tissue reserves of glycogen in gills and digestive gland. No significant alterations were observed in the assessed oxidative stress parameters so it was possible to hypothesize that the studied drugs may have probably exerted a limited alteration of antioxidant defenses and damage, which was reverted by the activation of defensive adaptive mechanisms. This set of data evidenced that the pro-oxidative metabolism that was already described for both drugs in other animal models, was not fully established in the exposed mussels. On the contrary, glycogen reserves were substantially changed after exposure to both toxicants, being possible to observe opposite responses caused by both drugs. Food uptake was not altered following exposure to the drugs. Further evaluations are thus required to conclude about both drugs ecotoxicity and other parameters, namely seasonality, which should be considered when performing ecotoxicology tests, especially with the selected species.